Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1177/10711007211002814
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiological Outcomes of Operative Therapy in Insertional Achilles Tendinopathy With Debridement and Double-Row Refixation

Abstract: Background: Insertional Achilles tendinopathy (IAT) is a painful pathology in which the strongest and thickest tendon of the human body is affected. Different conservative and operative treatments have been described to address this pathology. This study aimed to evaluate the medium-term clinical and radiological outcomes of patients who underwent a surgical therapy via a longitudinal tendon-splitting approach with debridement and double-row refixation. Methods: All patients were assessed pre- and postoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In fact, clinical evidence has presented that a conservative approach to tendon debridement may lead to recalcification of the anatomy. 9 To address this and to create a "worst-case" scenario for biomechanics, we performed a complete detachment of the tendon prior to repair as has been described in other cadaveric studies. 9 This allowed us to test the mechanism of failure of the anchors and tendon suture interface.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, clinical evidence has presented that a conservative approach to tendon debridement may lead to recalcification of the anatomy. 9 To address this and to create a "worst-case" scenario for biomechanics, we performed a complete detachment of the tendon prior to repair as has been described in other cadaveric studies. 9 This allowed us to test the mechanism of failure of the anchors and tendon suture interface.…”
Section: Discussionmentioning
confidence: 99%
“…Yontar et al 21 were able to follow their patients for five years on average and reported that 30 of 33 patients had excellent or good results with average preoperative and postoperative American Orthopaedic Foot and Ankle Society (AOFAS) scores of 55.8 and 92, respectively. Greiner et al 22 showed significant improvements in outcome scores in their series of 42 patients, using a double-row construct, but did show that lateral radiographs at 33-month follow-up showed recurrent calcification in 71.4% of patients.…”
Section: Detachment and Reattachmentmentioning
confidence: 94%
“…Rather than a limited approach, most surgeons use open surgical management involving calcaneoplasty, Achilles tendon débridement, bursal excision, and subsequent tendon reattachment. [17][18][19][20][21][22] This is most often performed with a central tendon-splitting approach described by McGarvey et al, 17 although paratendinous approaches exist. Ettinger et al treated 40 patients with this approach using a variety of different suture anchor techniques.…”
Section: Detachment and Reattachmentmentioning
confidence: 99%
“…Patient-reported outcomes related to quality of life at 1 year posttreatment and beyond have also been documented as significantly improved over preoperative scores following the use of a double-row suture fixation system. 5 The weakness of this double-row arrangement is its reliance on very distal grasp of the tendon, leaving the possibility of the sutures pulling through the longitudinally oriented fibers of the Achilles. 4…”
Section: Introductionmentioning
confidence: 99%
“…Patient-reported outcomes related to quality of life at 1 year posttreatment and beyond have also been documented as significantly improved over preoperative scores following the use of a double-row suture fixation system. 5 The weakness of this double-row arrangement is its reliance on very distal grasp of the tendon, leaving the possibility of the sutures pulling through the longitudinally oriented fibers of the Achilles. 4 We present a novel modification to optimize the technique for performing a double-row repair at the Achilles insertion by employing a knotless intrasubstance suture construct with a Bunnell formation delivering a more substantial anchoring system.…”
Section: Introductionmentioning
confidence: 99%